Studi Living Qur’an Dalam Tradisi Istighosah Sabtu Legi Di Pondok Pesantren Mamba’ul Hisan Kota Kediri - Yuliana Desi Rahmawati; Ahmad Syauqie Hidayat (Universitas Nahdlatul Ulama Blitar, 2021)
This study aims to examine the interaction of students at Mamba'ul Hisan Islamic Boarding House, Kediri City with the Qur’an in the form of routine Saturday legi istighosah. This study uses a qualitative descriptive analytical method with the Living qur’an method using a sociological, phenomenological, and psychological approach. This article showed that the students of Mamba'ul Hisan Islamic boarding house in Kediri City understand and explore the use and function of the verses of Qur’an used in the saturday legi istighosah routine and its context as a prayer.